New endophytic fungal species of Chaetomiaceae (Ascomycota) in Iraq - ALAA A. AL-RIFAIE; MOHANAD K. M. AMEEN (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Al-Rifaie AA, Ameen MKM. 2023. New endophytic fungal species of Chaetomiaceae (Ascomycota) in Iraq. Biodiversitas 24: 5270-5277. The present study was conducted to isolate and identify some endophytic fungi from vegetable crops in Iraq. Samples of eight vegetable plants, namely Abelmoschus esculentus, Mentha piperita, Vicia faba, Petroselinum sativum, Ocimum basilicum, Lawsonia inermis, Beta vulgaris and Apium graveolens were collected from three regions in Basrah (Abu Al-Khaseeb, Karmat Ali and the Centre of Basrah). Isolation was done by solid culture method and moist culture method. The recovered endophytic fungi were purified and axenic cultures of each isolated species were then identified on the basis of their macro and micro-morphological features. Morphological identification was further confirmed by molecular analysis through DNA extraction and sequencing by PCR amplification of the ITS4 and ITS5 gene primers. Phylogenetic examination revealed that five novel endophytic fungal species related to the family Chaetomiaceae were isolated from vegetable plants, including Chaetomium cucumericola, C. madrasense, Amesia atrobrunnea, A. cymbiformis and Botryotichum verrucosum. Three species, including C. cucumericola, A. cymbiformis and B. verrucosum, were documented for the first time in the Iraqi mycobiota. To the best of our acknowledgment, this study is the first to investigating endophytic fungi from vegetables in Iraq.